The Effect of Vitamin Premixes on The Physiological State of Broiler Chicks - Shakhlo Babaeva; Iminov Hijiakbar (American Journal of Biodiversity, 2025)
This article studies the effects of vitamin preparations on the physiological state of chicks. In addition, the physiological state of chicks was studied by comparing the effects of vitamin premixes given to chicks. This study explores the impact of vitamin premix supplementation on the physiological state and growth performance of broiler chicks during the early stages of development. Vitamin premixes, which include essential vitamins such as A, D, E, K, and B-complex, play a crucial role in metabolic regulation, immune function, and tissue development. In this experiment, chicks were divided into control and treatment groups, with the latter receiving a vitamin-enriched feed. Physiological indicators such as body weight gain, feed conversion ratio (FCR), hematological parameters, and immune responsiveness were measured over a 21-day period. The results demonstrated that chicks supplemented with vitamin premixes exhibited significantly improved growth performance, higher red and white blood cell counts, and enhanced antibody titers compared to the control group. These findings suggest that vitamin premixes contribute positively to the overall physiological health and productivity of broiler chicks.